Kajian Kinerja Terminal Batu Ampar Kota Balikpapan - Chikita, Randha Alief; Djakfar, Ludfi; Anwar, M. Ruslin (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2017)
Batu Ampar Terminal Balikpapan is the only type A passenger terminal in Balikpapan City. The purpose of this study is to determine the operational performance of the terminal at this time and also to determine the level of service in the terminal. The results of this study indicate that for FIFO queue discipline analysis on AKDP and AKAP bus lines, it is known that Ï <1 means that there is currently no queue in the terminal. For the analysis of terminal facilities it is known that there are still some terminal facilities that are not yet available from the main facilities and supporting facilities, therefore the need for additional facilities in order to meet the standard of passenger terminal type A. In the next 15 years analysis for traffic intensity value is approaching 1 which means in the future will cause the queue in the terminal, so it is necessary for the improvement of terminal performance. For the service performance with IPA method there are 35 variables that there are 7 variables that enter in quadrant I. In the next step to do analysis to know the priority of handling by using QFD method.Â